Humanization of prenatal care in the praxis of health professionals: introductory note - Camila Nunes Barreto; Luiza Cremonese; Lisie Alende Prates; Juliane Scarton; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2015)
Doi: 10.5902/2179769212970 Aim: to identify the process of approximation of the presuppositions of humanization and the public policies and health programs, proposed by the Ministry of Health, in the praxis of low-risk prenatal care. Method: descriptive field study, using a qualitative approach and anthropological perspective. The setting of the study will consist of Family Health Strategies. The subjects will be nurses and doctors who develop actions in the scope of prenatal care. Data will be collected through participant observation and semi-structured interview and, afterwards, analyzed using the operative proposal. Expected Results: this study is expected to promote discussions and reflections that promote the  understanding of the context of humanization in prenatal care and can contribute to the qualification of the care to pregnant women.